Negotiating Travel Constraints via Technology: A Study of Malay Muslim Women through a Hierarchical Constraint Model Perspective - Ratthinan, Senutha P.; Selamat, Nor Hafizah (MAG Scholar, 2019)
As a moderate Muslim nation, the mobility of Malay Muslim women in Malaysia is not legally restricted by the state. However, their movements are constrained by factors such as their roles, responsibilities, and the need to preserve values related to their religious and custom requirements. These constraints are shaped by patriarchal gender norms where women are expected to be obedient to a system of institutionalized male power. Our paper seeks to understand the constraints subjected to Malay Muslim women in travelling for leisure and study how they negotiate those constraints using technology. Based on ten qualitative, in-depth interviews conducted with Malay Muslim women aged between 22 to 37 years old, the findings showed that women are gaining the support, trust and freedom to travel via technology. Using the Hierarchical Constraint Model, the findings indicate that culture is significant wherein several constraints faced by MMW differ from those faced by Western or other Asian women. The new insights generated from this paper are unique as they reflect on the unexplored segment of Asian women where Malay Muslim women are becoming the testament of transformation. The finding indicates their departure from the gendered patriarchy norms as technology becomes their tool to negotiate constraints while facilitating the growth of female travel market. A significant association between travel constraints and negotiation illustrates that women are empowered by using technology to travel